Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1149/2.052203jes
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Phosphate Thin Films Grown by Atomic Layer Deposition

Abstract: Lithium phosphate, Li 3 PO 4 , has been considered a potential electrolyte material for lithium ion batteries and CO 2 sensors in particular if the films can be made dense and of high quality already at low thickness. In this work, Li 3 PO 4 thin films were deposited by atomic layer deposition (ALD) between 225 and 350 • C using trimethyl phosphate and either of the two lithium sources, namely lithium hexamethyldisilazide or lithium tert-butoxide. The deposited films showed slightly crystalline Li 3 PO 4 struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 36 publications
3
74
0
Order By: Relevance
“…Nevertheless, an ALD process for Li 3 PO 4 has been recently presented. 49 LiLaTiO x (LLT) also has been suggested as an electrolyte material, but this material has been reported to have high electrical conductivity, causing short-circuit issues. 50 Because of the small thickness envisioned for ALD deposited films an extremely low electrical conductivity is required.…”
Section: 43mentioning
confidence: 99%
“…Nevertheless, an ALD process for Li 3 PO 4 has been recently presented. 49 LiLaTiO x (LLT) also has been suggested as an electrolyte material, but this material has been reported to have high electrical conductivity, causing short-circuit issues. 50 Because of the small thickness envisioned for ALD deposited films an extremely low electrical conductivity is required.…”
Section: 43mentioning
confidence: 99%
“…ALD has emerged as the premier deposition process for fabrication of uniform, thin, conformal films on high aspect ratio scaffolds, 13−16 and ALD has previously been used to fabricate the solid electrolytes (Li,La) x Ti y O z , 17 Li 3 PO 4 , 18 Li x Al 2 O 3 , 19,20 and Li x Si y Al 2 O 3 . 21 Utilizing a unique integrated high-vacuum deposition, surface characterization, and battery assembly system, 22 we have developed a quaternary ALD process for the solid electrolyte LiPON.…”
mentioning
confidence: 99%
“…Li3PO4 can be deposited using either LiO t Bu or LiHMDS as the lithium source and TMPO (trimethyl phosphate, Figure 9) as the phosphate precursor [114,115]. The LiO t Bu + TMPO process showed a constant growth rate of approximately 0.7 Å/cycle between 225 and 275 °C [114].…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al [115] and Létiche et al [116] have studied the Li3PO4 process using LiO t Bu and TMPO in an effort to measure the lithium-ion conductivity of these films. Wang et al reported an increasing growth rate as a function of the deposition temperature at 250-325 °C, which might be a result of the somewhat unsaturative behaviour of the process [114]. Electrochemical impedance spectroscopy showed that the films had rather good conductivities when deposited at 300 °C: 3.3 × 10 −8 S/cm was extrapolated for a film with a composition of Li2.8POz (as determined by XPS) [115].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation